Sonographic-Assisted Catheter-Positioning in Intracerebral Hemorrhage - Niesen, Wolf-Dirk; Reinhard, Matthias; Gierthmuehlen, Mortimer; Fuhrer, Hannah (Frontiers in Neurology, 2018)
Introduction: Intracerebral structures and pathologies such as intracerebral hemorrhages (ICH) can be displayed sufficiently by transcranial sonography (TCS). In some patients with ICH clot evacuation via surgery or catheter drainage to reduce secondary parenchymal injuries may be necessary. We hypothesized that bedside-placement of drainage-catheters, which is a minimal invasive evacuation-technique complicated by a higher rate of catheter misplacement can be optimized via TCS. Methods: Eleven consecutive ICH-patients diagnosed via computertomography (CT) were included in this prospective observational pilot study. All patients were examined via TCS, firstly in order to illustrate the hematoma, secondly to optimize catheter placement. Catheter placement was primarily validated via CT. Results: The TCS-depiction of ICH-extension was optimal in 10 patients; one patient showed a partially insufficient transtemporal bone window. Catheter positioning could be traced and adapted correctly via TCS-examination in all patients. Follow-up CT-scans confirmed TCS-description of catheter-positioning in all patients without any complications. Reduction of symptoms and ICH-volumes confirmed effectiveness of treatment. Conclusions: The illustration of ICH and the drainage-placement is possible via TCS in a cost- and time-efficient way.